2015
DOI: 10.1378/chest.14-1297
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Mycobacterium abscessus Subspecies abscessus Isolation During Mycobacterium avium Complex Lung Disease Therapy

Abstract: BACKGROUND: Isolation of Mycobacterium abscessus subspecies abscessus (MAA) is common during Mycobacterium avium complex (MAC) lung disease therapy, but there is limited information about the clinical signifi cance of the MAA isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In previous studies of NTM lung disease caused by MAC or MABC, the range of reported prevalences of mixed infection by both pathogens was wide at 8% to 61%, depending on the study population and the definition of mixed infection (17,19,22,25). However, most of these studies evaluated the development of another infection during the disease course of the primary infection (17,19) or encompassed the past infection as well as a coexistent infection (22,25), whereas our study investigated only concomitant mixed infections.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In previous studies of NTM lung disease caused by MAC or MABC, the range of reported prevalences of mixed infection by both pathogens was wide at 8% to 61%, depending on the study population and the definition of mixed infection (17,19,22,25). However, most of these studies evaluated the development of another infection during the disease course of the primary infection (17,19) or encompassed the past infection as well as a coexistent infection (22,25), whereas our study investigated only concomitant mixed infections.…”
Section: Discussionmentioning
confidence: 92%
“…In a study of MAC lung disease, 29% (5/17) of the patients with nodular bronchiectatic MAC lung disease, but none with upper lobe cavitary disease, had M. abscessus infection (20). Another study of nodular bronchiectatic MAC lung disease also found that 29% of the subjects harbored M. abscessus during therapy for MAC lung disease (17). Similarly, in a study of M. abscessus lung disease in which nearly all (98%) of the study subjects had bronchiectasis and nodular opacities, the prevalence of coexistent or previous MAC infection was as high as 55% (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinfection with MAC and M. abscessus subsp. abscessus occurs and may be associated with new or enlarged cavities in case of additional M. abscessus -PD [59]. This underlines the necessity of regular microbiological and clinical follow-ups to determine which patients truly have M. abscessus -associated lung disease during the course of MAC-PD.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A recent report considered 53 patients encountered over a 12-year period who received treatment for MAC PNTM and had M abscessus subspecies abscessus ( Maa ) isolated during therapy. 40 …”
Section: Recent Insightsmentioning
confidence: 99%